Robust Randomized Controlled Data Is Lacking in Total Joint Arthroplasty - Chen, Zhongming; Bains, Sandeep S.; Hameed, Daniel; Dubin, Jeremy A.; Stern, Jonathan M.; Mont, Michael A. (The Journal of Knee Surgery, 2022)
Introduction Randomized controlled trials (RCTs)are regarded as highest level of scientific evidence. There is belief that while prospective randomized control trials (PRCTs) are the gold standard for evaluating efficacy of interventions, there are very few conducted on lower extremity joint arthroplasty. However, there was a more than adequate amount (n=197) of published RCTs in knee arthroplasty during the 2021 calendar year. Therefore, we studied RCTs on knee arthroplasties for 2021 and assessed them for overall study topic reasons (i.e., devices as well as prostheses, rehabilitation, pain control, blood loss [tranexamic acid], and other), which were then subcategorized by: (1) country of origin; (2) sample size; and (3)whether or not they were follow-up studies. After this, we specifically focused on the studies (n=26) concerning devices or prostheses.Methods A search of PubMed on “knee arthroplasty” specifying “RCT” using their search function and dates between January 1, 2021 to December 24, 2021 resulted in the analyzed reports. A total of 17.3% reports analyzed rehabilitation methods while 28.4% studied pain control. A total of 20.3% examined blood loss topics and 20.8% investigated other topics.Results We found that 26 studies (13.2%) involved prosthetic design and implantation. Overall, only 15% knee arthroplasty RCTs were conducted in the United States, the mean total final sample size was 133±146 patients, and 7% were follow-up studies. None of the prostheses studies were performed in the United States, and the mean total final sample size of all of these studies was 86±54 patients, and 23% were follow-up studies. Total knee arthroplasty prospective RCTs were not performed in the United States.Conclusion The authors believe that other study designs, such as database or registry analyses, are also appropriate in this rapidly advancing field of joint arthroplasty for the continuing evaluation and approval of new prostheses and techniques, while we await more PRCTs in our field.
Keywords: randomized controlled trial; orthopaedic; joint; knee; arthroplasty